Science and secularization. Issue 1 (2nd January 2017) - Harrison, Peter
ABSTRACT: According to a long-standing narrative of Western modernity science is one of the main drivers of secularization. Science is said to have generated challenges to core religious beliefs and to have provided an alternative, rational way of looking at the world. This narrative typically relies on progressive and teleological understandings of history, and commitment to some version of an ongoing struggle between science and religion. By way of contrast, recent theories of secularization, such as that of Charles Taylor, have suggested that the role of science in secularization has been greatly exaggerated. This article also offers a critique of the standard "science causes secularization" story. But in contrast to other critiques of this kind, it suggests that science nonetheless has a significant role in secularization – one that can be maintained without a commitment to a crude progressivist history or a narrative of science-religion conflict.